Does humor work in advertising of pharmaceutical products? - Bara, Carlos Roberto Francisco (2010)
This thesis aims to evaluate whether humorous television commercials (TVCs) work for non-prescription drugs, known as “over-the-counter” (OTC). The construct humor in advertising is controversial since it involves complex and broad typology, and depends on the audience characteristics. Several studies within different product categories indicated that some consumer goods are better suited for humorous TVCs, while others, such as OTC drugs, may not take advantage from it. Paradoxically, drug announcers spend billions of dollars worldwide in humorous OTC ads. An experiment with real consumers was designed as between-and-within-subjects, to test three hypotheses. Sixty women were exposed to pairs of humorous and non-humorous TVCs, for each of the three drug categories (analgesics, vitamins, and laxatives). We used fictional brand names and real ads, and measured four dependant variables: attitude toward the advertising (AAD), attitude toward the brand (ABR), purchase intention (PI), and brand choice (BC), after subjects being exposed to manipulations of two independent variables: humorous vs. non-humorous TV commercials, for the drug categories. Conditional logit model confirmed that humor does not help to persuade respondents, whose choices, attitudes, and purchase intention were less favorable with humorous TVCs, in comparison to non-humorous executions. Future research is presented regarding marketing for pharmaceutical products.